Situational efficacy of anthropomotor types of young female handball players - Srhoj, V. (Collegium Antropologicum, 2002)
A battery of 26 anthropomotor and 15 situational handball tests were used in a sample of 155 girls aged 13 years, attending Split handball school for 4 years, for taxonomization and determination of relations among the areas analyzed. Figures were analyzed by taxonomic analysis using the model of polar types and canonic correlation analysis. Five types that basically corresponded to the positions in the team were identified in the anthropomotor area: universal player, wing player, outside player, middle outside player and circular player. Situation-related types showed three ways of presenting specific handball activity defined by the level of complexity of realization of specific tasks: specific handball efficacy, specific hand coordination, and movement with changes of direction. Two types of integrating attitudes, i.e. two ways of solving complex tasks, were established by canonic relations between the anthropomotor and situational types. According to the first, the energy articulated as dynamic mass is used for the purpose of achieving general handball goals, and it is typical for all-round players and outside shooters. According to the other one, different kinds of movements are used to achieve the goals in handball, typical for wing players and middle outside attack players, characterized by regulation of direction changes and handling the ball.